2023
DOI: 10.54558/jiss.1114516
|View full text |Cite
|
Sign up to set email alerts
|

Ergenlerin Narsisizm Düzeylerinin Sosyo-Demografik Değişkenlere Göre İncelenmesi (Kayseri İli Örneği)

Abstract: Çalışmanın amacı, ergenlerin narsisizm düzeylerini belirlemektir. Araştırma tarama modelindedir. Araştırma, Kayseri İli merkez ilçelerinde öğrenim 21 ortaöğretim okullarındaki 1058 lise öğrencisinin katılımı ile gerçekleşmiştir. Öğrencilerin kişisel bilgilerini öğrenmek için kişisel bilgi formu, narsistik hayranlık ve rekabet özelliklerini değerlendirmek için “Narsistik Hayranlık ve Rekabet Ölçeği”nden yararlanılmıştır. Araştırmada kullanılan ölçeğe ilişkin geçerlik ve güvenirlik analizleri yapılmış olup; elde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In 2022, It was found that participants' depression, negative automatic thoughts and dysfunctional attitudes did not differ by gender. When the literature is examined, it confirms that depression, negative automatic thoughts, and dysfunctional attitudes do not differ according to gender (Bulut Serin and Aysan, 2021;Tümkaya and İflazoğlu, 2000;Topal, 2011). On the other hand, studies are showing that it differs according to gender (Lök and Bademli, 2017;Şahin and Sarı, 2010;.…”
Section: Methodsmentioning
confidence: 78%
“…In 2022, It was found that participants' depression, negative automatic thoughts and dysfunctional attitudes did not differ by gender. When the literature is examined, it confirms that depression, negative automatic thoughts, and dysfunctional attitudes do not differ according to gender (Bulut Serin and Aysan, 2021;Tümkaya and İflazoğlu, 2000;Topal, 2011). On the other hand, studies are showing that it differs according to gender (Lök and Bademli, 2017;Şahin and Sarı, 2010;.…”
Section: Methodsmentioning
confidence: 78%